Raising bilingual autistic children in the UK: at the intersection between neurological and language diversity - Digard, Bérengère Galadriel; Johnson, Ellie; Kašćelan, Draško; Davis, Rachael (Frontiers in Psychiatry, 2023)
Introduction While research shows no negative effects of bilingualism on autistic children’s development, due to misconceptions around both autism and bilingualism, bilingual parents and educational/clinical practitioners who advise them often express unfounded concerns that exposing autistic children to more than one language will cause confusion and developmental delays. To understand the reasons that drive these misconceptions, this study focuses on: identifying factors that impact family decisions about (not) raising autistic children bilingually; attitudes toward bilingualism expressed by the community, doctors, family members, and teachers; sources of information about bilingualism and autism available to families. Methods Through a mixed-method online survey, we explored these questions in 31 UK-based bilingual families with 34 autistic children (age M = 10.6 years; SD = 7.1). Results The families reported choosing bilingualism for their autistic child primarily so that the child can communicate with family and community members. Attitudes toward bilingualism in their networks were predominantly positive, with a large portion of individuals not having opinions possibly due to lack of information. Only about 1/3 of parents had access to information on bilingualism and autism, mostly found on the internet. Discussion We discuss these findings and offer future directions for research, practice, and battling stigmas around bilingualism and autism.